Algoritmos para geração de reticulados conceituais - Sérgio Mariano Dias (2010)
Concept lattices are used in formal concept analysis for knowledge representation. Formal concept analysis was born in 1982 with the work presented by Wille [1982], who proposed to consider each lattice element as a formal concept and the lattice as a hierarchy of relationships between concepts. Currently there is a growing interest in formal concept analysis applications in many science areas. However, the concept lattice can behave (number of formal concepts) exponentially. Although this behavior is rarely found in practical cases, yet the computational cost can be prohibitive for many applications, thus creating the need for new algorithms to build concept lattices and approaches to reduce this complexity. This paper presents two proposals for reducing the concept lattices complexity and discusses a methodology for evaluating such proposals. It proposes an educational framework to develop algorithms for formal concepts analysis called EF-Concept Analysis (Educational Framework for Concept Analysis) and present a benchmark for valuationof constructing concept lattices paradigms, which can be expanded and used by the scientific community.